Response of Potato Cultivars to Phosphate Fertilization in Tropical Soils with Different Phosphorus Availabilities - Fernandes, Adalton M. [UNESP]; Soratto, Rogério P. [UNESP] (Springer Nature, 2016)
Potato cultivars have different strategies for dealing with phosphorus (P) deficiency in soil, and their response to P fertilization may vary because of differences in soil P availability. This study was performed to evaluate the effect of P fertilization rates (0, 125, 250, 500, and 1000 kg P2O5 per hectare) on the P uptake, fertilizer P recovery, tuber yield, and applied P use efficiency of five potato cultivars (Agata, Asterix, Atlantic, Markies, and Mondial) grown in Oxisols with low, medium, and high P availability in southeastern Brazil. The tuber yield of all potato cultivars increased similarly with increase in P fertilizer application up to rates of 500, 250, and 125 kg P2O5 per hectare in the soils with low, medium, and high P availability respectively. This increase was found despite the leaf P concentrations being lower than the deficiency limit of 2.5 g kg−1 only in the soil with low P availability in the absence of P fertilizer application. The application of phosphate fertilizer in the planting furrow resulted in a greater increase in the leaf P concentration, plant growth, P uptake, number of tubers per plant, tuber mean weight, tuber yield, and P removal of the potato crop grown in the soil with low P availability compared with soils with high P availability. In soil with high P availability, P application rates higher than 125 kg P2O5 per hectare did not increase the number, size, and yield of tubers. The cultivar Mondial had the highest tuber yield, fertilizer P recovery, and applied P use efficiency, especially at the lower P application rates, but at a specific initial P availability, all cultivars responded to the same P application rate. The results indicate that phosphate fertilizer recommendations should be adjusted on the basis of soil P availability, and that it is not necessary to use different criteria to evaluate the P-nutritional status for individual potato cultivars.
Keywords: Applied phosphorus use efficiency; Fertilizer phosphorus recovery; Phosphorus removal; Phosphorus uptake; Solanum tuberosum; Tuber yield